Relationship between government’s capacity to tax and infant health in Brazil : evidence from the Tax Capacity Program PMAT - Vizcaino, Carlos Andres Charris (2021)
This thesis studies the effect of changes in the government’s tax-capacity on infant health outcomes. We exploit a program that invests in the tax capacity of Brazilian municipalities.Using variations in the timing of program uptake, we study the effects of this policy on infant health. We find (I) that the program is robustly correlated with improvement in tax revenues, public spending on education and health, night-lights density, the total number of health sector workers, high school dropouts rates, and the homicide rate per 1000 inhabitant and (II) the policy also improved infant health outcomes measured by low birthweight (LBW) and infant mortality. Summarizing, our results indicate a positive effect of the implementation of the tax capacity program on child health, and these results can be explained by the improvement observed in the fiscal and development outcomes, and mother’s health behavior. Given the existence of a large “fiscal gap” between local expenditure responsibilities and local tax revenues, our results are important to consolidate the decentralization process. Keywords: Tax capacity. Infant mortality. Infant health at birth. Public spending.